COMMUNICATION STRATEGY OF THE INDONESIAN RED CROSS ORGANIZATION IN MEDAN CITY IN INCREASING PUBLIC BLOOD DONOR PARTICIPATION - Wasiyem, Wasiyem; Sitepu, Dhea Salsabila Br.; Sari, Fhidiana; Wardani, Icha Febi; Syafira, Listi Tri; Friska, Mutia; Saragih, Nazla Novrinda; Rahma, Putri Aulia; Ananda, Riska; Fahny, Vira Zul (HEARTY, 2025)
The need for blood in Medan City continues to increase every year, but has not been matched by the level of community participation in voluntary blood donation. This research aims to analyze the communication strategies applied by the Indonesian Red Cross (PMI) Medan City in increasing public awareness and participation in blood donation. This research used a qualitative method with a descriptive approach, which involved in-depth interviews with five informants, consisting of PMI internal parties and the general public. The results showed that PMI Medan City implemented various communication strategies, including persuasive and humanist communication, utilization of social media and conventional media, and the AIDDA model approach (Awareness, Interest, Desire, Decision, Action). In addition, PMI actively collaborates with various parties and emphasizes friendly service to build public trust. Obstacles faced include a lack of public understanding, negative perceptions, and fear of the blood donation process. Effective, educative, and targeted communication strategies are proven to increase public participation and shape PMI's positive image as a humanitarian organization. The findings recommend the importance of innovation and continuous evaluation in communication strategies to address challenges in the field and strengthen the culture of voluntary blood donation.